Establishing calculation method for chemical composition of primitive magma in the Cenozoic in South Central coast region and the adjacent continental shelf of Vietnam - Anh, Le Duc; Hoang, Nguyen; Phach, Phung Van; Malinovskii, A. I.; Shakirov, Renat; R., Kasatkin S.; V., Golozubov V.; Nam, Bui Van; Dong, Mai Duc; Huong, Ngo Bich; et al. (Vietnam Journal of Marine Science and Technology, 2019)
The calculations which determine the chemical composition of the primitive magma are simple but they show changes in the temperature and pressure states of the magma source. The method is based on the addition of the chemical composition of the Olivine to the major element composition of the eruptive rocks which follows the formula: Ci = Ci-1+ 0.1 * Ci-1Ol. In accordance with the characteristics of the study area, we have made new additions to the calculation method. The calculation results are highly accurate when tested and compared with the chemical composition of the eruptive rocks. The chemical composition of the primitive magma solution is used to calculate the temperature and pressure states in the magma source. The results show that there is a difference in temperature and pressure in the source at different tectonic positions in the study area. Accordingly, the South Central coast region and the adjacent continental shelf are divided into two main types of eruptions. The first type of volcanic eruptions occurs at locations where major faults intersect and they are located north of the study area. The second type of volcanic eruptions in the form of a single volcano is located to the south of the study area and the southeastern continental shelf, and occurs in intracontinental extension structure